PERBANDINGAN MEDIA TANAM DAN PEMBERIAN POC URIN SAPI DALAM PENINGKATAN KESUBURAN TANAH PADA GRAFTING TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Amanda, Ricky Ryan; Tarigan, Ruth Riah Ate; Warsito, Kabul (Agros Journal of Agriculture Science, 2024)
The aim of this research is to determine the comparison of giving planting media and cow urine in increasing soil fertility in grafting grape plants (vitis vinifera) in the pre-nursery and their interactions. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed. Factor I studied consisted of R0 = 0 kg/plot, R1 = 1 top soil: 1 rice husk/plot, R2 = 2 top soil: 1 rice husk/plot, R3 = 1 top soil: 2 rice husks/plot. Factor II treatment of giving cow urine POC consisted of S0 = 0 mL/liter of water/plot, S1 = 10 mL/liter of water/plot, S2 = 15 mL/liter of water/plot. The parameters observed were plant height, shoot height, number of leaves, number of stem segments, stem diameter and number of tendrils. The results of the research showed that the provision of planting media had a real influence on the parameters of plant height, shoot height, number of leaves and number of stem segments, but the parameters of stem diameter and number of tendrils showed no real influence. Cow urine POC showed a real influence on the parameters of plant height, shoot height, number of leaves, and number of stem segments, but the parameters of stem diameter and number of tendrils showed no real influence.Key words: planting media, cow urine POC, grape plants INTISARITujuan penelitian ini adalah untuk mengetahui perbandingan pemberian media tanam dan poc urine sapi dalam peningkatan kesuburan tanah pada grafting tanaman anggur (vitis vinifera) di pre nursery berserta  interaksinya. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK)  Faktorial terdiri dari 2 faktor dengan 12 kombinasi perlakuan dan 3 ulangan sehingga diperlukan 36 plot. Faktor I yang diteliti terdiri R0= 0 kg/ plot, R1 = 1 top soil : 1 sekam padi/plot, R2 = 2 top soil : 1 sekam padi/plot, R3 = 1 top soil : 2 sekam padi/plot. Faktor II perlakuan pemberian POC urine sapi terdiri S0 = 0 mL/liter air/Plot, S1 = 10 mL/liter air/plot, S2 = 15 mL/liter air/plot. Parameter yang diamati adalah Tinggi Tanaman, tinggi tunas, jumlah daun, jumlah ruas batang, diameter batang  dan jumlah sulur. Hasil penelitian menunjukan pemberian media tanam memberikan pengaruh nyata pada parameter Tinggi tanaman, tinggi tunas, jumlah daun, dan jumlah ruas batang,tetapi pada parameter diameter batang dan jumlah sulur menunjukan pengaruh yang tidak nyata. POC urine sapi menunjukan pengaruh nyata pada parameter Tinggi tanaman, tinggi tunas, jumlah daun, dan jumlah ruas batang,tetapi pada parameter diameter batang dan jumlah sulur menunjukan pengaruh yang tidak nyata. Kata kunci: media tanam, POC urine sapi, tanaman anggur